2020
DOI: 10.22159/ijpps.2020v12i5.37209
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Various Scales Used in Causality Assessment of Adverse Drug Reactions

Abstract: Establishing a relationship of causality between the medications received and the events occurred utilizing causality assessment scale is much needed to reduce the occurrence of Adverse Drug Reactions (ADRs) and to prevent exposure of patients towards additional drug hazards. Causality assessment can be defined as the determination of chance, whether a selected intervention is the root cause of the adverse event observed. The causality assessment is the responsibility of either a single expert or an establishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…In our study, we observed an incidence of adverse drug reactions (ADRs) at a rate of 2.75%, constituting a significant portion, specifically 47.01%, of the total DRPs. This trend aligns with findings from two other studies, where they reported similar ADR incidences of 2.17% 19 and 1.82%, respectively 20,21 . There was an another study reported a lower incidence of 3.7% ADRs among hospitalized patients in India, highlighting the need to investigate the reasons for this discrepancy, including under-reporting and inadequate pharmacovigilance systems 22 .…”
Section: Resultssupporting
confidence: 92%
“…In our study, we observed an incidence of adverse drug reactions (ADRs) at a rate of 2.75%, constituting a significant portion, specifically 47.01%, of the total DRPs. This trend aligns with findings from two other studies, where they reported similar ADR incidences of 2.17% 19 and 1.82%, respectively 20,21 . There was an another study reported a lower incidence of 3.7% ADRs among hospitalized patients in India, highlighting the need to investigate the reasons for this discrepancy, including under-reporting and inadequate pharmacovigilance systems 22 .…”
Section: Resultssupporting
confidence: 92%
“…This is very important in ensuring safer health services, as 1-10% of medication errors identified in patient care are associated with patient harm [4]. There are different scales in assessing causality in adverse drug reactions, such that when that is introduced in the curriculum, the students may be better positioned to identify the adverse drug reactions errors [35].…”
Section: Discussionmentioning
confidence: 99%